Analisis Hukum Partisipasi Masyarakat Dalam Proses Pembentukan Peraturan Perundang-Undangan - Izza Difanda Hanania (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2025)
This research aims to analyze community participation in the process of forming laws and regulations and the obstacles that accompany it. Community participation in the process of forming laws and regulations is a concrete manifestation of the implementation of sovereignty which is in the hands of the people. Regulations regarding community participation are regulated in Article 96 of Law Number 13 of 2022 which is an amendment to Law Number 12 of 2011. This regulation accommodates community participation which can be provided by providing written and verbal input, both online and offline regarding each stage of formation. The research uses normative methods and a legislative and conceptual approach that examines related laws and regulations descriptively. The research results show that community participation can be channeled through listening meetings, outreach, work visits, and various other forms of discussions facilitated by the government. However, in implementing community participation, normatively there are still several obstacles or evaluations regarding regulations, namely (1) limitations in the meaning of